Cloud Point Extraction Based on Binary Surfactants for Separation, Preconcentration and Spectrophotometric Determination of Beryllium with 1,8-Dihydroxy Anthrone - BEIRAGHI, ASADOLLAH; BABAEE, SAEED (Asian Journal of Chemistry, 2010)
A new micelle-mediated phase separation of metal ions, using mixed micelles of the cationic surfactant cetyl pyridinium chloride (CPC) and non-ionic surfactant Triton-X- 114, applied for preconcentrating trace levels of beryllium as a prior step to its determination by spectrophotometry has been developed. Beryllium was compelexed with 1,8- dihydroxy anthrone in an aqueous surfactant medium and it was concentrated in the surfactant rich phase after separation. The chemical variables affecting the cloud point extraction (e.g., pH, surfactant and reagent concentrations, temperature, incubation and centrifuge times) were evaluated and optimized. Under the optimum experimental conditions, calibration graph was linear in the range of 2-120 ng mL-1 with detection limit of 0.2 ng mL-1 and the precision (% RSD) for 5 replicate determinations at 60 ng mL-1 of Be(II) was 0.16 %. In this manner the preconcentration and enrichment factors were 25 and 14.2, respectively. The interference effect of some cations and anions was also studied. Finally, the proposed method was successfully applied to the determination of beryllium in synthetic and real water samples.